2008
DOI: 10.1002/jclp.20442
|View full text |Cite
|
Sign up to set email alerts
|

Delusional disorder–jealous type: how inclusive are the DSM–IV diagnostic criteria?

Abstract: Delusional disorder-jealous type is a new diagnostic category in the Diagnostic and Statistical Manual for Disorders, Fourth Edition, Text Revision (DSM-IV-TR; American Psychiatric Association, 2000) in which delusions concerning a partner's infidelity must be present. Therefore, patients who experience a jealousy disorder, but do not experience delusions will not fit the diagnostic criteria. Using a database of 398 case histories of jealousy disorders reported in the literature from 1940-2002, we examined the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…The Morbid Jealousy Database consists of data coded by trained coders who reliably coded data across cases and variables (see Easton et al 2007Easton et al , 2008. Chi-square analyses were used to test predictions at α=0.05.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Morbid Jealousy Database consists of data coded by trained coders who reliably coded data across cases and variables (see Easton et al 2007Easton et al , 2008. Chi-square analyses were used to test predictions at α=0.05.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate a large sample of individuals diagnosed with morbid jealousy, we used the Morbid Jealousy Database (see Easton et al 2007Easton et al , 2008 for details). The database includes 398 case histories, of which 298 are men diagnosed with morbid jealousy and 100 are women diagnosed with morbid jealousy.…”
Section: Participantsmentioning
confidence: 99%
“…Interestingly, Easton, Shackelford, & Schipper (2008) analysed 398 cases of PJ published between 1940 and 2002 and reported that only 4% fulfilled all criteria of Delusional Disorder-Jealous Type. They conclude that the current DSM IV criteria which require a delusion of infidelity exclude many non-delusional cases which are sufficiently severe to need treatment, and suggest a more broadly defined jealousy disorder category for future DSM editions.…”
Section: Diagnostic Status Of Delusional Jealousymentioning
confidence: 99%
“…In delusional jealousy, they are egosyntonic, regarded as true and not resisted, and the diagnosis depends on the factors summarised in 2.2. So far, there is no well-defined diagnostic category for non-delusional cases (s. Easton et al, 2008). Jealousyrelated cognitions which are experienced as egodystonic, unwanted, senseless or irrational and are resisted strongly resemble obsessions.…”
Section: Diagnostic Status Of Non-delusional Pathological Jealousymentioning
confidence: 99%
“…The Diagnostic and Statistical Manual for Disorders, Fourth Edition, Text Revision (DSM-IV-TR) defines clinical jealousy as a delusional disorder-jealousy type [8]. A diagnosis of delusional disorder-jealous type requires that “an individual experiences persistent, unrelenting content-specific delusions of a partner’s infidelity that cannot be explained by a conjoint history of schizophrenia, drugs, or physical illness [6,8]. Delusional disorder-jealous type diagnoses occur at an estimated prevalence of less than 1% of the world population [8].…”
Section: Introductionmentioning
confidence: 99%